What Matters in Corporate Governance? - Bebchuk, Lucian; Cohen, Alma; Ferrell, Allen (Review of Financial Studies, 2009)
We investigate the relative importance of the twenty-four provisions followed by the Investor Responsibility Research Center (IRRC) and included in the Gompers, Ishii, and Metrick governance index (Gompers, Ishii, and Metrick 2003). We put forward an entrenchment index based on six provisions: staggered boards, limits to shareholder bylaw amendments, poison pills, golden parachutes, and supermajority requirements for mergers and charter amendments. We find that increases in the index level are monotonically associated with economically significant reductions in firm valuation as well as large negative abnormal returns during the 1990–2003 period. The other eighteen IRRC provisions not in our entrenchment index were uncorrelated with either reduced firm valuation or negative abnormal returns.